2018
DOI: 10.1186/s12879-018-3431-z
|View full text |Cite
|
Sign up to set email alerts
|

Reactive plasmacytosis mimicking multiple myeloma associated with SFTS virus infection: a report of two cases and literature review

Abstract: BackgroundSevere fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease caused by a novel bunyavirus named SFTS virus (SFTSV), which is classified into the genus Phlebovirus and family Phenuiviridae. Reactive plasmacytosis mimicking multiple myeloma is a very rare condition in association with SFTS. Here, we describe two SFTS cases who presented with hyperimmunoglobulinemia, as well as extensive bone marrow and peripheral blood plasmacytosis, which mimicked multiple myeloma (MM).Case pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The low susceptibility to SFTSV of B cells and plasmablasts obtained from healthy individuals seems to contradict results showing that B cells in autopsy tissues are highly susceptible to SFTSV. Our previous results and those of other studies have demonstrated that plasmablasts appear transiently in the peripheral blood during the acute phase of SFTS (27,51,52). In addition, the peripheral-blood plasmablasts proliferate to a greater extent in fatal SFTS than those in self-limiting SFTS, and the massive proliferated plasmablasts in fatal SFTS are dysfunctional (27).…”
Section: Discussionmentioning
confidence: 49%
“…The low susceptibility to SFTSV of B cells and plasmablasts obtained from healthy individuals seems to contradict results showing that B cells in autopsy tissues are highly susceptible to SFTSV. Our previous results and those of other studies have demonstrated that plasmablasts appear transiently in the peripheral blood during the acute phase of SFTS (27,51,52). In addition, the peripheral-blood plasmablasts proliferate to a greater extent in fatal SFTS than those in self-limiting SFTS, and the massive proliferated plasmablasts in fatal SFTS are dysfunctional (27).…”
Section: Discussionmentioning
confidence: 49%
“…Numerous studies have reported that compared with healthy subjects, the level of B cells was markedly elevated and positively correlated with the severity of SFTS disease (94,96,125,126). Further studies revealed that the peripheral blood mononuclear cells of patients with SFTS could induce propagation of atypical lymphocytes in vitro, and these transient atypical lymphocytes were activated B cells generated by stimuli other than virus particles, which were released by SFTSV-infected B cells, indicating that SFTSV-infected B cells release factors that cause B cells to differentiate into plasmablasts (118,(126)(127)(128). By contrast, a previous cohort investigation study found that the number of B cells was markedly reduced during the first week of infection but quickly returned to normal levels in patients with SFTS (95).…”
Section: T-cell-mediated Immune Response To Sftsv T Lymphocytes Serve...mentioning
confidence: 99%
“…2 , 3 , 6 Interestingly, these same cytokines are linked to the proliferation, differentiation, and survival of plasma cells. 7 , 8 Immunologically, plasma cells are responsible for synthesizing antibodies and have been identified as possibly producing virus-neutralizing antibodies in COVID-19. 9 , 10 Not only have plasma cells been noted in bronchoalveolar lavage (BAL) fluid 11 and gross lung pathology 12 in COVID-19, but plasmablast expansion and extrafollicular B cell activation has also been described in patients who are critically ill. 13 Interestingly, plasmablast frequency in patients with severe COVID-19 did not correlate with age, days since symptom onset, comorbidities, or levels of receptor binding domain specific IgM or IgG.…”
Section: Introductionmentioning
confidence: 99%